Increased Risk of Inflammatory Bowel Disease Among Patients With Ankylosing Spondylitis: A 13-Year Population-Based Cohort Study - Wang, Shuya; Tsou, Hsi-Kai; Chiou, Jeng-Yuan; Wang, Yu-Hsun; Zhang, Zhiyi; Wei, James Cheng-Chung (Frontiers in Immunology, 2020)
Abstract Aim: Ankylosing spondylitis (AS) primarily affects the axial skeleton and extraarticular structures. Small-scaled studies have reported that the incidence and prevalence of inﬂammatory bowel disease (IBD) are higher in patients with AS than in the general population. This study determined the incidence of IBD in patients with AS using a large scale population-based cohort dataset. Methods: This was a retrospective cohort study. Patient data were collected from the Taiwan National Health Insurance Research Database from 2000 to 20132. We enrolled 3804 patients with AS and 7608 non-AS patients. The endpoint was IBD diagnosis by using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) coding 555 and 556 after at least three outpatient visits or one hospital admission, until the end of 20132. The Kaplan–Meier analysis was performed to discriminate the cumulative incidence of IBD and the log-rank test was used to test the significance. A Cox proportional hazard model was used to estimate the hazard ratio (HR) for IBD between the AS and non-AS groups. Results: Among the population as a whole Tthe Cox proportional hazard regression indicated that patients aged ≥65 years [adjusted HR (aHR): 2.48, 95% confidence interval (CI): 1.38–4.47] or with comorbidity of cancer (aHR: 3.51, 95% CI: 1.40–8.80) had a higher HR for IBD. Kaplan–Meier curves of cumulative incidence proportion of IBD indicated that patients with AS had a higher risk of IBD than the non-AS group in the subgroup aged <40 years (HR: 2.85, 95% CI: 1.51–5.40, p = 0.001). Conclusions: Patients with AS aged <40 years had a higher IBD risk than did those without AS in Taiwan. Clinicians and patients should be aware of this association. Keywords: Musculoskeletal disorders, Inflammatory bowel disease, Rheumatology